Consuming your Way to Efficiency: Public Goods Provision through Non-Distortionary Tax Lotteries - Thomas Giebe; Paul Schweinzer (Center for Economic Studies and ifo Institute (CESifo), 2013)
We revisit the classical result that financing a pure public good through taxation of private consumption is inefficient. To this standard setup we add a consumption contest in which consumers can win a prize. We show that an appropriately chosen contest - which we call a 'tax lottery' - can correct the distortion in private consumption while, at the same time, inducing efficient provision of the public good and balancing the government's budget. The result does not depend on whether the public good is provided exogenously or dependent on actual tax revenue. We show that neither pure fundraising contests nor a sales tax combined with a 'simple' lottery can induce efficiency in the standard environment.
Keywords: C70; D70; H00; 330; public goods; taxation; contests; lotteries